The Influence of Electronic Word of Mouth (EWOM) Implementation on Purchasing Decisions at The Jungle Waterpark Bogor - Mohammad, Salma Nabila; Darmawan, Haryadi; Trihayuningtyas, Endah (Journal of Tourism Sustainability, 2023)
This study examines the influence of Electronic Word of Mouth (eWOM) on purchase decisions at The Jungle Waterpark Bogor. Stemming from a decline in visits due to the COVID-19 pandemic, this study employs a quantitative method with a survey approach. Data was collected through questionnaires from 150 respondents who are potential visitors or have previously visited the waterpark. The multiple linear regression analysis results with T-test and F-test indicate that eWOM significantly influences purchase decisions (significance value = 0.000). Nevertheless, specific dimensions of eWOM, such as platform assistance, social benefit, and advice-seeking, do not influence purchase decisions. This study provides valuable insights for digital marketing efforts and promotions addressing the pandemic's impact on the tourism industry.